The Role of Service Culture and Organizational Climate in Healthcare Workforce Digital Adaptation Readiness at the MAS Clinic in Banjarbaru, Indonesia - Martin Agusta; Adhika Ramadhan; Novia Purnamasari; Rahma Wahdiniwaty; Deden A. Wahab Sya’roni (Manunggal Halim Jaya, 2026)
Digital transformation through Electronic Medical Records (EMR) is an urgent need for primary-level healthcare facilities to improve service quality in the 4.0 era. However, the effectiveness of this technology is often hampered by suboptimal Human Resources (HR) readiness and support from the work environment, particularly in regional primary clinics. This study aims to analyze the role of service culture and organizational climate in the digital adaptation readiness of healthcare workers at the MAS Clinic in Banjarbaru. This study used a descriptive qualitative approach with a case study design. Data collection was conducted through in-depth interviews, observations, and documentation with 12 informants consisting of clinic leaders, doctors, nurses, and administrative staff. The results show that a service culture oriented towards professionalism, collaboration, and commitment to service quality are the main factors driving the acceptance of digital technology. In addition, a supportive organizational climate, especially through direct support from leadership, plays a role in helping healthcare workers overcome digital competency barriers. However, the digital adaptation process still faces several challenges, such as limited technological infrastructure, resistance to change, and low digital literacy. Healthcare workers' digital adaptation readiness depends not only on technological aspects, but also on strengthening the service culture and creating a conducive organizational climate. This study recommends the need for improved technology infrastructure and ongoing digital training at the MAS Banjarbaru Clinic to align conventional work culture with an integrated health information system.